THE ANALYSIS OF INTERNET SERVICES USING ANALYTICAL HIERARCHY PROCESS METHOD IN MANADO (CASE STUDY: TELKOMSEL, XL AND 3) - Lumempouw, F. Geraldy; Pangemanan, Sifrid S.; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Internet has become important things in human lives. Nowadays, some of people added internet as their primary needs. Consumer purchase decision is the process involved when individuals or groups select, purchase, use or dispose products, services or experience and ideas to satisfy their needs It is important because in understanding customer decision making, we will understand how consumer make the purchase decision, how the process of decision making by customer from searching until selecting the product or service, and also we can know the factors that influence the decision making. Based on five criteria (restaurant price, usefulness, ease of use, enjoyment and speed), speed become the most influence to attract consumer followed by price. This research used quantitative method. Quantitative research seeks to quantify the data. The method used in this research is Analytical Hierarchy Process (AHP). AHP is a method for ranking decision alternatives and selecting the best one given multiple criteria. It allows users to assess the relative weight of multiple criteria or multiple options against given criteria in an intuitive manner.Keywords: customer decision making, analytical hierarchy process